Nghiên cứu thành phần hóa học cây xàng dùng cambốt (Arnicratea cambodiana (Pierre) N. Hall.), họ cây gối (Celastranceae) - Hoàng, Vũ Đình; Tố Uyên, Đào Thị; Điền, Phạm Gia (Vietnam Journal of Chemistry, 2014)
Maytensifolin B, α–amyrin and clerolsterol were isolated from stem bark of Arnicratea cambodiana (Pierre) N. Hall. for the first time. Their structures were elucidated by means of spectroscopic methods and comparison with reported data.